2005
DOI: 10.1177/147322970500900106
|View full text |Cite
|
Sign up to set email alerts
|

The Mater Hospital Multiprofessional Care Pathway for Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is a common condition associated with an increasing mortality and morbidity. There are also significant economic implications with hospital admission accounting for the majority of the total COPD health care expenditure. Mild exacerbations of COPD can be treated at home; severe exacerbations require hospitalization. The purpose of this programme of care was to integrate and optimize treatment using current guidelines. Methods: This was a prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Due to limited statistical analysis and weak study design, the internal validity of results is limited 12–15. Our study confirmed that the implementation of a CP significantly reduces the 30 days readmission rate 32,33…”
Section: Discussionsupporting
confidence: 81%
“…Due to limited statistical analysis and weak study design, the internal validity of results is limited 12–15. Our study confirmed that the implementation of a CP significantly reduces the 30 days readmission rate 32,33…”
Section: Discussionsupporting
confidence: 81%
“…McManus et al noted that their score-based admission decision model was associated with a 4% drop in 1-month readmission rate and a 57% reduction in-hospital mortality. 41 Admission through to discharge [37][38][39][40][41][42] Admission through to discharge 46 Discharge planning [43][44][45] Admission through to discharge 48 49 Intervention elements Multidisciplinary team design 29-33 35 Initial assessment or investigation 29 30 35 36 Initial treatment or medication 29 30 34-36 Respiratory specialist consultation 29-31 35 36 Patient education [31][32][33] Discharge planning 31-33 35 36 Specialist service referral (eg, smoking cessation, occupational therapy) 29 31-36 Follow-up plan [31][32][33][34][35] Multidisciplinary team design 37 40-42 44 Assessment/investigation at presentation 40 Assessment/investigation at admission 37 39 41 Initial or ongoing treatment/medication prompts 37 38 40-42 Patient education 38 40-42 Specialist service referral (eg, smoking cessation, occupational therapy) [37][38][39][40][41][42] Disch...…”
Section: Care Pathwaysmentioning
confidence: 99%
“…Vanhaecht et al used QI methods and an auditfeedback approach to help hospital teams to understand care processes within their setting, to identify gaps in care and to generate plans for improvement. 38 Audit was also used by McManus et al 41 The designated coordinator role aided pathway compliance, 37 39 41 however, difficulties arose if an AECOPD admission was not identified, and therefore, did not receive standardised care. 39 42 Two papers noted attributed enhanced teamwork practices and reduced patient anxiety to implementation of the care pathway.…”
Section: Care Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now two non-randomized trials about the impact of a care pathway for inpatient management of COPD exacerbation are published [ 26 , 27 ]. The studies have been conducted between 2000 and 2001, and the methodology was rather weak.…”
Section: Introductionmentioning
confidence: 99%